Optimasi edible film dari pati singkong dan gelatin tulang ayam dengan penambahan ekstrak andaliman - Annatasya Risqa Erde; Elisa Julianti; Hotnida Sinaga (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
Biodegradable and environmentally friendly edible films can maintain product quality, replace the use of plastic packaging, and reduce the environmental pollution. This research utilized cassava starch, chicken bone gelatin, and andaliman extract as the ingredients of edible films. The aim of this research was to optimization the best edible film formulation through the physical (brightness, water vapor transmission rate, and thickness), mechanical (tensile strength and elongation), microbiology (inhibition of S. aureus and E. coli), and chemical (antioxidant) characteristics of edible film. The method used in this research was the Response Surface Methodology-Box Behnken Design (RSM-BBD) with Design Expert v.12 software. There were 3 factors used a minimum and maximum limit, namely cassava starch (2-4 %), chicken bone gelatin (2-4 %), and andaliman extract (3-6 %). The response variable optimization resulted in a new formula with a percentage of 4 % cassava starch, 3.879 % chicken bone gelatin, and 6% andaliman extract with a desirability level of 0.820.